Myeloid sarcoma with acute myeloid leukaemia: a case report of rare presentation - John, Anosh; Zafar, Amjad; Saleem, Ammara; Siddiqi, Harris; Bano, Kausar (Journal of the Pakistan Medical Association, 2025)
Myeloid sarcoma (MS) is a rare extramedullary manifestation of acute myeloblastic leukaemia (AML). The presentation of MS depends on the anatomical location being affected. Myeloid sarcoma can also occur in the absence of AML, but when they occur simultaneously, they are often associated with a poorer prognosis. We report the case of an adolescent patient of AML with MS of cervical lymph nodes presenting with vague and non-specific complaint of abdominal pain for two months with history of a non-specific and non-healing skin lesion on the right lower extremity. Detailed history and physical examination were a major help. Bone marrow biopsy and cervical lymph node biopsy were performed to make the definitive diagnosis. Chemotherapy and supportive care were administered. Since such cases are rarely encountered, they tend to be misdiagnosed. Reporting cases with such variable presentations can help physicians not to miss such important differential diagnoses in their evaluation. Keywords: Acute myeloblastic leukaemia, Acute myeloid sarcoma, Cervical lymphadenopathy.